Towards understanding healthcare professionals’ adoption and use of technologies in clinical practice: using Qmethodology and models of technology acceptance - Ladan, Muhammad Awwal; Wharrad, Heather; Windle, Richard (BCS, The Chartered Institute for IT, 2018)
Background: Globally, technologies have been recognised to improve productivity across different areas of practice including healthcare. This has been achieved by the expansion of computers and other forms of information technologies (IT). Despite this advancement, there have also been growing challenges to the adoption and use of these technologies within practice sometimes with unintended or unexpected consequences. However, the barriers and drivers to IT, and more specifically e-health adoption within healthcare are little understood, especially in areas such as Sub-Saharan Africa (SSA) where e-health adoption is relatively new. Methodology: This paper describes a pilot study to develop and validate sample statements for use within a later substantive Q-methodology study. The aim of the main study was to understand factors that influence healthcare professionals’ (HCPs) attitudes towards IT adoption and use in SSA. We report on the use of this methodology to explore the subjectivity of HCPs together with the models of technology acceptance (Technology-Acceptance-Model: TAM and the Unified-Theory-of-Acceptance-and-Use-of-Technology: UTUAT) used in combination for the first time. Results: Following various stages and mapping of the two models of technology acceptance used, forty-six statements were developed at the end of the pilot study. These statements were grouped into six themes to capture the constructs of the two models used in the study. Conclusion: Findings suggest it is possible to use TAM and UTAUT to develop a comprehensive set of statements. These statements reflect choices that HCPs consider on IT/e-health adoption and use in SSA which can be used in a Q study. Keywords: E-health, Q-methodology, Healthcare professionals, Technology Acceptance Model, Unified Theory of Acceptance and Use of Technology, Sub-Saharan Africa.